2021
DOI: 10.3389/fmolb.2021.568868
|View full text |Cite
|
Sign up to set email alerts
|

MICAL2 Facilitates Gastric Cancer Cell Migration via MRTF-A-Mediated CDC42 Activation

Abstract: Aims and Hypothesis: Cell migration is driven by the reorganization of the actin cytoskeleton. Although MICAL2 is known to mediate the oxidation of actin filaments to regulate F-actin dynamics, relatively few studies have investigated the potential role of MICAL2 during cancer cell migration.Methods: The migratory ability of gastric cancer cells was measured by wound healing and transwell assays. The relationship between MICAL2 expression and MRTF-A nuclear localization was analyzed using gene overexpression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Of note, MICAL1 exerts its effect on proliferation via reactive oxygen species (ROS)-sensitive PI3K/AKT/ERK signaling in breast cancer cells [ 33 ]. Similarly, MICAL2-induced ROS generation has also been reported to enhance the migratory potential of gastric cancer cells [ 34 ]. MICAL-L2 lacks the FAD domain and cannot generate ROS [ 35 ], and although several studies have suggested that MICAL-L2 may positively influence cancer progression [ 10 , 13 , 36 ], whether and how MICAL-L2 may be involved in this process remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, MICAL1 exerts its effect on proliferation via reactive oxygen species (ROS)-sensitive PI3K/AKT/ERK signaling in breast cancer cells [ 33 ]. Similarly, MICAL2-induced ROS generation has also been reported to enhance the migratory potential of gastric cancer cells [ 34 ]. MICAL-L2 lacks the FAD domain and cannot generate ROS [ 35 ], and although several studies have suggested that MICAL-L2 may positively influence cancer progression [ 10 , 13 , 36 ], whether and how MICAL-L2 may be involved in this process remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Variants of Formins also have been identified in human microcephaly patients( 23, 24, 38 ). MRTF is a downstream effector of Formin/Diaphanous-mediated actin dynamics for regulating the transcription of cell motility- and proliferation-related genes in tumor cells and fibroblasts( 8789 ). We found that microcephaly-like phenotype in the larva carrying loss-of-function allele of dia can be suppressed by Mrtf overexpression in NSCs, suggesting that Dia-Mrtf signaling plays an important role during brain development.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, miR-155 suppresses the expression of SOX1 to promote gastric cancer cell migration. 511 Furthermore, Wang et al 512 showed that MICALC2-mediated upregulation of nuclear MRTF-A promotes CDC42 activation, MMP9 expression, and gastric cancer cell migration. 512 …”
Section: Diseases Associated With Mutation Of Transcription Co-activa...mentioning
confidence: 99%
“… 511 Furthermore, Wang et al 512 showed that MICALC2-mediated upregulation of nuclear MRTF-A promotes CDC42 activation, MMP9 expression, and gastric cancer cell migration. 512 …”
Section: Diseases Associated With Mutation Of Transcription Co-activa...mentioning
confidence: 99%
See 1 more Smart Citation